Literal Meaning of Nur (the Light) Verse: Examining Unity of Being in the Translation of the Qur'an - Ammar Fauzi; Abdullah Abdul Kadir; Robby Habiba Abror; Cipta Bakti Gama (Buletin Al-Turas, 2022)
PurposeStarting from the consensus of the principal Sufi scholars and non-Sufi scholars in affirming Tawhid as a religious principle and the Qur’an as the main reference, this paper focused on the doctrine of Sufism through Nur (the Light) Verse. The study aimed to enhanced their agreement through the literalism method, even in its most elementary form, namely literal translation.MethodUsing the literal translation method, the study tried to answer whether Wahdatul Wujud could be explored and confirmed by the literal translation of the Light verse. Besides helping to clarify Wahdatul Wujud, it also confirmed the Sufi’s doctrine through comparing its results with other verses.Results/FindingsThe study pointed out that the doctrine of Wahdatul Wujud could be explained and elaborated through the literal translation of the Light verse; the explanation of Wahdatul Wujud confirmed its difference from the doctrine of hulul and ittihad; and the explanation and argumentation of Wahdatul Wujud did not only clear up misunderstandings but also opened the opportunity to reduce the tension between Sufi and others due tothe polemic of the doctrine.ConclusionThe literal translation needs to be further examined for its application to verses other than the light verse referred to by the Sufis in explaining Wahdatul Wujud or other Sufism doctrines such as the concept of heresy (al-dhalal), the concept of injustice (al-dzulm), infidel, shirk, agnoseology (al-ta'thil), and the degree of essence (maqam al-dzat).